The Adoption of e-Procurement in the Indonesian Public Sector - Napsah, Muhibuddin (Curtin University, 2016)
The adoption of electronic procurement (e-procurement) can provide strategic, operational and tactical benefits. Within Indonesia there has been a paucity of research that has examined how the benefits that can materialize from e-procurement can be obtained. This research determines the underlying variables that influence the successful adoption within the public sector. The identified variables are used to develop a benefits realisation management framework that can be used to support change management and organisational learning.